Evaluation of online clinical pharmacology curriculum resources for medical students. Issue 11 (6th September 2019) - Zhang, Xi Yue; Holbrook, Anne M.; Nguyen, Laura; Lee, Justin; Al Qahtani, Saeed; Garcia, Michael Cristian; Perri, Dan; Levine, Mitchell; Patel, Rakesh V.; Maxwell, Simon
Abstract : Aims: To identify and evaluate clinical pharmacology (CP) online curricular (e‐Learning) resources that are internationally available for medical students. Methods: Literature searches of Medline, EMBASE and ERIC databases and an online survey of faculty members of international English language medical schools, were used to identify CP e‐Learning resources. Resources that were accessible online in English and aimed to improve the quality of prescribing specific medications were then evaluated using a summary percentage score for comprehensiveness, usability and quality, and for content suitability. Results: Our literature searches and survey of 252 faculty (40.7% response rate) in 219 medical schools identified 22 and 59 resources respectively. After screening and removing duplicates, 8 eligible resources remained for evaluation. Mean total score was 53% (standard deviation = 13). The Australian National Prescribing Curriculum, ranked highest with a score of 77%, based primarily on very good ratings for usability, quality and suitable content. Conclusion: Using a novel method and evaluation metric to identify, classify, and rate English language CP e‐Learning resources, the National Prescribing Curriculum was the highest ranked open access resource. Future work is required to implement and evaluate its effectiveness on prescribing competence.